Hepatoprotective effect of Cichorium Intybus linn (Kasni) Extracts against Carbon Tetrachloride induced Liver Damage - Nadeem Naseem ,Malik Shah Zaman Latif ,Munir Tahir , Abdul Khalique Naveed ,Maqbool Hassan (Journal of Rawalpindi Medical College, 2009)
Background: To assess the effect of aqueous and alcoholic extracts of Cichorium intybus linn , frequently used by Hakims and traditional healers, on liver, against the carbon tetrachloride (CCl4) induced hepatic injury. Methods: In this experimental intervention study, forty rats were subdivided into four sub groups, ten in each group. Group I was kept as standard control. For this study three groups (II, III, IV) were made in which aqueous and alcoholic extract was given prior to hepatic damage by CCl4. Hepatoprotective effect was assessed by measuring serum levels of alanine transaminase(ALT), aspartate transaminase (AST) and alkaline phosphatase (ALP). Results: Very significant hepatoprotective effect (p<0.001) was observed by alcoholic extract while aqueous extract showed no significant effect against CCl4 induced hepatic injury. Conclusion: Alcoholic extract of Cichorium intybus linn exhibits a very significant hepatoprotective effect